Performance analysis of SLA - QoS UPE Metro Ethernet / Akmarul Nizam Zainudin - Zainudin, Akmarul Nizam (2014)
A Service Level Agreement (SLA) between a service provider and its customers will assure customers that they can get the service they pay for and will obligate the service provider to achieve its service promises. Failing to meet SLAs could result in serious financial consequences for a provider. Hence, service providers are interested in gaining a good understanding of the relationship between what they can promise in an SLA and -what their IT is capable of delivering. Similarly, consumers are interested in understanding the impact of the SLAs they sign on their own productivity. In this paper, we presented several measurement techniques to verify the guaranteed QoS for customer satisfaction based on the acceptable standard values